Influence of personality, attitude, motivation, and environment on the entrepreneurial spirit of school cooperative teachers in vocational schools in Kulon Progo regency - Triatun, Triatun; Sukidjo, Sukidjo (Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
This study aims to determine the influence of personality, attitude, motivation, and environment on the entrepreneurial spirit both partially and simultaneously. The research method uses a survey with 39 teachers of school cooperatives and respondents numbering 33 people. Primary data was obtained using questionnaires supported by observations and interviews on cooperative teachers and related parties: data analysis using descriptive statistics and multiple regressions with t-test and F tests. The results showed that personality, attitude, motivation, and the environment simultaneously and partially influenced positively and significantly the entrepreneurial spirit. The four variables contributed to the entrepreneurial spirit by 80.30%, while factors outside the research influenced 19.70%. The environment is the variable that contributes the most to the entrepreneurial spirit with a percentage of 23.52%, followed by personality by 20.91%, motivation 19.88%, and attitude 15.99%.